MARKETING STRATEGY ANALYSIS OF SAVINGS PRODUCTS AT PT BANK MUAMALAT KCP WIYUNG - Fahrur Rosi; Dian Berkah; Rukhul Amin (RADJA PUBLIKA, 2025)
This study examines the implementation of savings product marketing strategies at PT Bank Muamalat KC Wiyung and its impact on increasing the number of customers and savings funds. In-depth interviews were conducted with the branch managers of Bank Muamalat Wiyung to obtain an overview of how the bank markets savings products and the challenges faced in implementing them. The results of the study indicate that a combination of marketing strategies through sharia channels such as branch offices and digital such as mobile banking and the use of referral programs can effectively attract new customers and retain old customers. In addition, the implementation of a personal approach through direct visits and promotional campaigns strengthens customer relationships with the bank. However, the bank still faces challenges from intense competition and difficulties in introducing new products to an increasingly growing market. This study highlights the importance of managing innovative and sustainable marketing strategies, and how this can increase customer loyalty and the competitiveness of Bank Muamalat's savings products in the sharia banking market.